AFISsys - An autonomous instrument for the preservation of brackish water samples for microbial metatranscriptome analysis. (1st February 2019) - Charvet, Sophie; Riemann, Lasse; Alneberg, Johannes; Andersson, Anders F.; von Borries, Julian; Fischer, Uwe; Labrenz, Matthias
Abstract: Microbial communities are the main drivers of biogeochemical cycling of multiple elements sustaining life in the ocean. The rapidity of their response to stressors and abrupt environmental changes implies that even fast and infrequent events can affect local transformations of organic matter and nutrients. Modern molecular techniques now allow for monitoring of microbial activities and functions in the environment through the analysis of genes and expressed genes contained in natural microbial assemblages. However, messenger RNA turnover in cells can be as short as 30 seconds and stability varies greatly between transcripts. Sampling of in situ communities involves an inevitable delay between the collection of seawater and the extraction of its RNA, leaving the bacterial communities plenty of time to alter their gene expression. The characteristics of microbial RNA turnover make time-series very difficult because samples need to be processed immediately to limit alterations to the metatranscriptomes. To address these challenges we designed an autonomous in situ fixation multi-sampler (AFISsys) for the reliable sampling of microbial metatranscriptomes at frequent intervals, for refined temporal resolution. To advance the development of this instrument, we examined the minimal seawater volume necessary for adequate coverage of community gene expression, and the suitability of phenol/ethanol fixation for immediate and long-term preservation of transcripts from a microbial community. We then evaluated the field eligibility of the instrument itself, with two case studies in a brackish system. AFISsys is able to collect, fix, and store water samples independently at a predefined temporal resolution. Phenol/ethanol fixation can conserve metatranscriptomes directly in the environment for up to a week, for later analysis in the laboratory. Thus, the AFISsys constitutes an invaluable tool for the integration of molecular functional analyses in environmental monitoring in brackish waters and in aquatic environments in general. Graphical abstract: Image 1 Highlights: An autonomous water in situ fixation multi-sampler (AFISsys) has been designed. AFISsys collects, fixes, stores water samples independently off-shore at high temporal resolution. AFISsys conserves sensitive mRNA directly in the environment for up to a week. Metatranscriptome analysis feasible with 250 mL of water volumes. Integration of molecular functional analyses in environmental monitoring in aquatic environments feasible.